Primary Merkel Cell Carcinoma: A Retrospective Analysis of 31 Cases in Poland - Magdalena Ciążyńska; Katarzyna Szczepaniak; Marta Pabianek; Dariusz Nejc; Adam Reich; Małgorzata Ułańska; Witold Owczarek; Małgorzata Skibińska; Joanna Narbutt; Aleksandra Lesiak (Adis, Springer Healthcare, 2020)
Abstract Introduction Merkel cell carcinoma (MCC) is a rare, aggressive cutaneous neuroendocrine cancer that typically arises in sun-exposed areas of the skin, especially in the elderly. Significant advances have recently been made regarding skin cancers, but data on cases of MCC are rather limited as these patients are frequently grouped together with other non-melanoma skin cancers (NMSC). Here, we performed an analysis of the clinical profile of patients with MCC in Poland to identify major factors influencing the prognosis. Methods Approximately 13,000 pathology and medical records were examined to identify patients with MCC diagnosed between 2010 and 2019. The management and outcomes of patients with histologically confirmed MCC were retrospectively evaluated. Results Thirty-one patients diagnosed with MCC were identified. The tumor occurred predominantly in women (61.3%) and in the elderly (mean 75.6 years). Twenty-nine patients had locoregional MCC and two had metastatic MCC at the time of diagnosis. Patients in stage I disease had excellent prognosis. In stages II and III, respectively 22.2% and 50.0% of patients developed metastases. Among patients who received chemotherapy with cisplatin and etoposide, 17% achieved partial remission with progression-free survival (PFS) of 8.0 months, and a further 50% achieved stable disease with PFS of 4.0, 4.5, and 4.5 months respectively. In 6 (19.4%) patients MCC coexisted with chronic lymphocytic leukemia (CLL). In all six cases CLL preceded MCC development. Conclusions Female gender, tumor-free resection margins, and local disease were found to be independent prognostic factors in MCC progression. Patients with hematological malignancies, immunosuppression, and those with immune deficiencies should be closely followed up as they are predisposed to develop MCC.